Extreme Basicity of Biguanide Drugs in Aqueous Solutions: Ion Transfer Voltammetry and DFT Calculations - Langmaier, Jan; Pižl, Martin; Samec, Zdeněk; Záliš, Stanislav (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2016)
Ion transfer voltammetry is used to estimate the acid dissociation constants Ka1 and Ka2 of the mono- and diprotonated forms of the biguanide drugs metformin (MF), phenformin (PF), and 1-phenylbiguanide (PB) in an aqueous solution. Measurements gave the pKa1 values for MFH(+), PFH(+), and PBH(+) characterizing the basicity of MF, PF, and PB, which are significantly higher than those reported in the literature. As a result, the monoprotonated forms of these biguanides should prevail in a considerably broader range of pH 1-15 (MFH(+), PFH(+)) and 2-13 (PBH(+)). DFT calculations with solvent correction were performed for possible tautomeric forms of neutral, monoprotonated, and diprotonated species. Extreme basicity of all drugs is confirmed by DFT calculations of pKa1 for the most stable tautomers of the neutral and protonated forms with explicit water molecules in the first solvation sphere included.